Advanced glycation end products and their adverse effects: The role of autophagy. Issue 4 (28th January 2021) - Sruthi, C. R.; Raghu, K. G.
Abstract: The critical roles played by advanced glycation endproducts (AGEs) accumulation in diabetes and diabetic complications have gained intense recognition. AGEs interfere with the normal functioning of almost every organ with multiple actions like apoptosis, inflammation, protein dysfunction, mitochondrial dysfunction, and oxidative stress. However, the development of a potential treatment strategy is yet to be established. Autophagy is an evolutionarily conserved cellular process that maintains cellular homeostasis with the degradation and recycling systems. AGEs can activate autophagy signaling, which could be targeted as a therapeutic strategy against AGEs induced problems. In this review, we have provided an overview of the adverse effects of AGEs, and we put forth the notion that autophagy could be a promising targetable strategy against AGEs.